Serum E3 SUMO-protein ligase NSE2 level and peroxynitrite related to oxidative stress in nephrolithiasis patients - Mehde, Atheer Awad; Yusof, Faridah; Mehdi, Wesen Adel; Ahmed Raus, Raha; Othman Farhan, Layla; Zainulabdeen, Jwan Abdulmohsin; Zainal Abidin, Zaima Azira; Ghazali, Hamid; Abd Rahman, Azlina (Elsevier BV, 2016)
Objective: To prove probable relations between serum E3 SUMO-protein ligase NSE2 (NSMCE2) concentration, peroxynitrite related to oxidative stress in nephrolithiasis patients. Methods: A total of 60 patients with nephrolithiasis and 50 healthy volunteers were involved in this study. Colorimetric method was used to detect blood urea, creatinine, uric acid, protein, albumin, total antioxidant status, total oxidant status, peroxynitrite, nitric oxide and oxidative stress index. Glutathione, NSMCE2 and superoxide dismutase were measured by ELISA. Results: A significant increase in level of peroxynitrite, total oxidant status, NSMCE2 and oxidative stress index in patients was observed, while total antioxidant status and glutathione were significantly decreased. Conclusions: The study concluded that serum NSMCE2 significantly correlated with peroxynitrite and oxidative stress in patients with nephrolithiasis.